Case Report: A novel PHOX2B p.Ala248_Ala266dup variant causing congenital central hypoventilation syndrome - Artamonova, Irina N.; Zlotina, Anna M.; Ismagilova, Olga R.; Levko, Tatyana A.; Kolbina, Natalia Yu; Bryzzhin, Aleksandr V.; Smorodin, Andrey P.; Borodin, Alexandr V.; Mamaeva, Ekaterina A.; Sukhotskaya, Anna A.; Kagantsov, Ilya M.; Malysheva, Daria A.; et al. (Frontiers in Pediatrics, 2023)
Introduction. Congenital central hypoventilation syndrome, CCHS, is a rare disease characterized by central alveolar hypoventilation and impaired autonomic regulation, caused by a mutation in PHOX2B gene. More than 90% of patients have a PARM (polyalanin repeat mutation) in the heterozygous state, characterized by the expansion of GCN repeats and an increase in the number of alanine repeats, so that genotypes 20/24 - 20/33 are formed (the normal genotype is 20/20). The remaining 10% of the PHOX2B gene contains NPARM (non-PARM) mutations. Case description. We present a clinical case of a girl with a novel PHOX2B heterozygous genetic variant in the exon 3: NM_003924.4:c.733_789dup:p.Ala245_Leu263dup. The duplication includes 16 GCN (alanine) repeats and 3 adjacent amino acids. Both clinically healthy parents demonstrated a normal PHOX2B sequence. Besides the girl has a pathogenic mutation in RYR1 gene and variant of unknown significance in NKX2-5 gene. The child’s phenotype is quite special. She needs ventilation during sleep, and has Hirschsprung's disease type I, arterio-venous malformation S4 of the left lung, ventricular and atrium septal defects, coronary-right ventricular fistula, hemodynamically non-significant, episodes of sick sinus and atrio-ventricular dissociation with bradycardia, divergent alternating strabismus OU retinal angiopathy. Two episodes of hypoglycemic seizures were also registered. Severe pulmonary hypertension resolved after appropriate ventilation adjustment. Dyagnostic odyssey was quite dramatic. Conclusion. Detection of a novel PHOX2B mutation expands understanding of molecular mechanisms of CCHS, and genotype-phenotype correlations.